PL02 Breastfeeding and Social Mobility: Neurological Development or Stress Mechanisms?. (17th September 2012) - Sacker, A; Kelly, Y; Bartley, M; Iacovou, M
Abstract : Background: Breastfeeding has been associated with higher cognitive scores, better test results and fewer socio-emotional problems in childhood. These outcomes in turn predict social mobility. This study examines the effect of breastfeeding on inter-generational social mobility and the role of two biologically plausible mechanisms: via improved neurological development due to the long-chain polyunsaturated fatty acids in breast milk and via hypothalamic-pituitary-adrenal (HPA) axis functioning due to growth hormones in breast milk. Methods: We use data from two birth cohorts (the 1958 National Child Development Study and the 1970 British Birth Cohort) to examine breastfeeding's relationship with social mobility. Social class at 10/11 years was based on father's class. Both class of origin and own social class in adulthood (age 33/34) were measured by the Registrar General's social class (RGSC). Neurological development was assessed using cognitive tests and assessments of fine motor function. HPA functioning was assessed using socio-emotional behaviour scales and a physical symptoms of stress score. Results: Rates of breastfeeding were higher in the 1958 cohort than the 1970 cohort (43% vs. 21% breastfed 1+ months). Breastfeeding was more socially patterned by 1970, with advantaged mothers being more likely to breastfeed. A propensity score approach matched breastfed and non-breastfed children on a large number of characteristics before estimating the effect of breastfeeding on social mobility. We modelled the odds of upward and downward social mobility conditional on being breastfed for 1 month or more and social class of origin. Results show that breastfeeding increased the odds of upward mobility (1958 cohort: OR 1.25 95% CI 1.13, 1.37; 1970 cohort: OR 1.14 95% CI 1.00, 1.31), and reduced the odds of downward mobility (1958 cohort: OR 0.81 95% CI 0.74, 0.90; 1970 cohort OR 0.79 95% CI 0.69, 0.91). Controlling for the measures of neurological development and stress functioning attenuated the effect of breastfeeding to marginal or non significance. Gender differences in these findings will be discussed. Conclusion: Breastfeeding promotes upward social mobility and protects against downward mobility. The effects appear to operate through enhanced neurological development and more effective stress processes.